Margy Gerber, et al., eds.: Studies in GDR Culture and Society 8. Selected Papers from the Thirteenth New Hampshire Symposium on the German Democratic Republic - Karen Remmler (GDR Bulletin, 1990)
Lanham: University Press of America, 1987. 206 p.